Is it worth the wait? Should Chloroquine or Hydroxychloroquine be allowed for immediate use in CoViD-19? - Syed Shahzad Hasan; Chia Siang Kow; Hamid A Merchant (British Journal of Pharmacy, 2020)
The growing CoViD-19 (novel coronavirus disease 2019) pandemic and the number of deaths is becoming a big concern across the world. There is a need for an immediate therapeutic solution to prevent the spread of the disease further and prevent the number of CoViD-19 associated deaths across the world. The healthcare professionals and the public at large are asking questions about the evidence surrounding the use of chloroquine (CQ) and hydroxychloroquine (HCQ) in the management of CoViD-19. Both CQ and HCQ had been recently used clinically across the world to treat severe pneumonia associated with COViD-19, however, the evidence is very weak due to the lack of randomised clinical trials and misinterpretation of clinical evidence by the non-scientific community. This article presents a critical review of clinical and scientific evidence around the use of CQ and HCQ in CoViD-19 available to date and highlighted the issues concerning the safety and toxicity of CQ/HCQ if permitted for general use by the public. Due to lack of evidence around CQ/HCQ in preventing the CoViD-19, its potential risk of fatal cardiac arrhythmia, and greater risk of self-use and harm in the developing world, it is recommended that the use of CQ/HCQ should only be initiated by specialist clinician dealing with CoViD-19 outbreak to treat CoViD-19 associated pneumonia under close cardiac monitoring.